EFFECTS OF SEED PREPARATION, SOWING MEDIA, SEED SOWING RATE AND HARVESTING PERIOD ON THE PRODUCTION OF CHIA MICROGREENS - Anjana Junpatiw (My University, 2019)
Chia (Salvia hispanica L.), a species of seeds with high essential fatty acids and nutraceutical content has encouraged increased crop production worldwide.Keeping value-added products in consideration, four experiments were conducted with the CRD method.In the first experiment, seed preparation was done by soaking the seeds in water, followed by sowing them in media.In the first treatment, T1, seeds were sown without soaking.In T2, seeds were sown after being soaked for 6 hours at room temperature (temperature) and, in T3 for 12 hours.In T4, after being soaked at 70-80°C, the seeds were allowed to cool down at room temperature for 6 hours and in T5 for 12 hours, before sowing.According to the results, T4 treatment produced the highest germination percentage, microgreen height and fresh weight.In the second experiment, seeds were sowed in 5 different seeding medias for 7 days.The mix of coconut coir with sand and rice husk ash (1:1:1) produced the highest percentage of germination, microgreen height and fresh weight.The third experiment was conducted to study the best seed sowing rate amongst 56, 93, 130, 167 and 204 g/m 2 .The results showed that the seed sowing rate of 204 g/m 2 gave the highest fresh weight.The fourth experiment was to study the effect of harvesting period, by focusing on the harvesting periods of 5, 6, 7, 8 and 9 days, after sowing.The results showed that the period of 6-9 days after sowing gave the highest fresh weight.
Keywords: Food and Agricultural Sciences